Analysis of Productivity and Welfare of Oil Palm Farmers through Sustainable Islamic Banking Financing in Cooperatives in Riau and East Kalimantan Provinces - Okky Fahrizal Achmad; Susy Muchtar (Budapest International Research and Critics University, 2023)
The research only discusses all subjects in the Cooperative on Productivity and Welfare of Oil Palm Farmers through Sustainable Islamic Banking Financing at Danau Lancang Indah Cooperative and Sawit Etam Bersama Cooperative in the Riau and East Kalimantan Provinces. And to what extent the application of the distribution of INTI Plasma product financing has been carried out by cooperative management for sustainable economic growth (SDGs). By using descriptive qualitative research methods and using content analysis techniques. The results of this study indicate that the existence of a financing distribution programme is very supportive of oil palm farmers even though there are several things that are not optimal, it must be evaluated and improved in order to achieve sustainable development (SDGs).